1973
DOI: 10.1677/joe.0.0590295
|View full text |Cite
|
Sign up to set email alerts
|

PLASMA OESTRADIOL-17β AND ITS RELATIONSHIP TO SERUM FOLLICLE-STIMULATING HORMONE IN IMMATURE FEMALE RATS

Abstract: Oestradiol-17\g=b\(E2) was measured by radioimmunoassay in the plasma of immature female rats. Maximal E2 levels of 55\p=n-\60 pg/ml were found at 10\p=n-\15 days of age; from day 25 to day 35 E2 levels were low to undetectable. The E2 measured appeared to be of ovarian origin: ovariectomy performed on day 13 resulted in a decreased E2 level 2 days later (13 pg/ml) as compared with the value from the control litter mates (46 pg/ml); after adrenalectomy the level of circulating E2 remained normal (54 pg/ml). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
3

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 12 publications
4
43
0
3
Order By: Relevance
“…Thus, early studies by Jost [45] and Pfeiffer [74] showed that fetal or neonatal gonadectomy did not interfere with the female differentiation of the genitals thereby setting the basis for the concept of a default developmental program in the female. Estrogen levels are shown to be very high during fetal development [104] as well as during early postnatal life [65] in females. It was thus assumed that ovariectomy would render the developing female free from circulating estrogens.…”
Section: The Role Of the Ovary In Female Sexual Differentiationmentioning
confidence: 99%
“…Thus, early studies by Jost [45] and Pfeiffer [74] showed that fetal or neonatal gonadectomy did not interfere with the female differentiation of the genitals thereby setting the basis for the concept of a default developmental program in the female. Estrogen levels are shown to be very high during fetal development [104] as well as during early postnatal life [65] in females. It was thus assumed that ovariectomy would render the developing female free from circulating estrogens.…”
Section: The Role Of the Ovary In Female Sexual Differentiationmentioning
confidence: 99%
“…immature rats, the ovary in females (Meijs-Roelofs et al 1973) and the adrenal gland in females and males (Baird et al 1969, Weisz & Gunsalus 1973 have been postulated for a long time as the source of E 2 ; however, it is difficult to explain the developmental change of serum E 2 levels. Recently, it was reported that the stomach is one of the extraovarian tissues synthesized and secreted by E 2 , and the E 2 levels in the portal vein are over ten times higher than those in the artery in normal conditions of adult male rats (Ueyama et al 2002, 2004, Kobayashi et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…2c) (Meijs-Roelofs et al, 1973;Weisz & Gunsalus, 1973;Cheng & Johnson, 1974) as is the decrease in serum high-affi¬ nity oestrogen-binding protein (EBP) concentrations from 5 to 20 days of age and its absence thereafter (Nunez et al, 1971;Raynaud et al, 1971;Raynaud, 1973 (MacKinnon et al, 1976). A further indication of the increasing concentrations of free and physiologically active oestradiol in the blood is the increase in weight of the uterus from about 26 days of age which has been reported by Price (1947) (1976) have shown that both albumin and SHBG decreased the uptake of testosterone by the prostate expiants in direct proportion to the fraction of unbound testosterone in the superfusion medium.…”
Section: Uterine Uptake Of[3h]oestradiolmentioning
confidence: 99%
“…There is an apparent paradox in the hormone patterns of developing female rats in that concentrations of total serum oestradiol and follicle-stimulating hormone (FSH) are high until about 21 days of age when the levels of both hormones decrease (Meijs-Roelofs, Uilenbroek, de Jong & Welschen, 1973;Weisz & Gunsalus, 1973;Cheng & Johnson, 1974). This apparent lack of negative steroid feedback on FSH output may, however, be accounted for by the presence of a protein (alpha-fetoprotein) in the serum of young rats which has a high affinity for oestrogen and which decreases from birth to about 23 days of age (Nunez et al, 1971; Raynaud, MercierBodard & Baulieu, 1971;Raynaud, 1973).…”
Section: Introductionmentioning
confidence: 99%